COMPARISON OF LEGAL SOCIAL SECURITY PROTECTION ON MIGRANT WORKER IN INDONESIA AND MALAYSIA - Nelly Zarnida; Eka Kurniasari (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2021)
This thesis examines the comparison of social security protection for migrant workers in Indonesia and Malaysia, by looking at the current law. This research uses normative legal research or also known as library research, in which to achieve the objectives of this study an analysis of both countries law and international legal instruments is carried out. The results of this study found that since early 2019 the Malaysian government has provided social security for foreign workers under a government organization, namely Social Security Organization (SOCSO), while Indonesia has already enacted a social security protection for foreign workers under a government organization, namely Social Security Organizing Agency (BPJS) in 2011. From this research it is also found that Indonesia has similarities and differences in legal arrangements regarding social security for foreign workers, namely placing social security for Migrant workers under state organizations, and equally not providing pension security to foreign workers.Keyword: Social security protection, Socso, Bpjs